FINE NEEDLE ASPIRATION CYTOLOGY: SENSITIVITY AND SPECIFICITY IN THYROID LESIONS - Musani, Mohammed Ayub; Khan, Faheem A.; Malik, Shoukat; Khambaty, Yousuf (Journal of Ayub Medical College Abbottabad, 2011)
Background: Thyroid enlargement is one of the common problems in patients presenting at outpatients department of ENT particularly in females. Thyroid nodules are common, thyroid cancer is uncommon and the most common way for it to present is as a solitary thyroid nodule. This study was conducted to evaluate the sensitivity and specificity of Fine Needle Aspiration Cytology (FNAC) in thyroid diseases. Method: This prospective analytic study was conducted at ENT Department of Karachi Medical and Dental College/Abbasi Shaheed Hospital during year 2004-8. One hundred and five cases were enrolled who underwent thyroid surgery after complete evaluation by history, clinical examination, Thyroid profile, Thyroid Scintigraphy, Ultrasound neck and FNAC. In cases which were revealed malignant by FNAC, CT scan were done to see the extent of disease and neck node status. Surgery was done in all cases and specimens sent for histopathology. Results: Male to female ratio of the patients was 1:8.5. Most common lesion was benign nodule (96). Malignant lesions were 9 in FNAC. In histopathology, the benign nodules were 92, and malignant cases were 13. Sensitivity of FNAC was 61.53% and specificity was 98.9%. Conclusion: FNAC in Thyroid has high sensitivity and specificity. Keywords: FNAC, Thyroid, nodule, malignant, cytology